The effect of a probiotic, KE-01, and Neoterramycin on nursery pig growth performance - Frantz, N.Z.; Nelssen, Jim L.; DeRouchey, Joel M.; Goodband, Robert D.; Tokach, Michael D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A 35-d growth study with a total of 168 weanling pigs (21 ± 2 d of age) was conducted to determine the effects of feeding a probiotic, (KE-01) and an antibiotic, Neoterramycin (neomycin 140 g/ton, oxytetracycline 140 g/ton), on nursery pig performance. Experimental treatments were arranged in a 2 × 2 factorial with main effects of antibiotic (none or neomycin 140g/ton and oxytetracycline 140g/ton) or probiotic (none or KE-01, 0.35%). KE-01 is a probiotic containing a novel strain of lactobacillus casei. A KE-01 by Neoterramycin interaction was observed for ADFI (P<0.05) from d 14 to 35, but no other interactions were detected. From d 0 to 14, pigs fed diets containing Neoterramycin had improved (P<0.01) ADG, ADFI, and F/G compared with those of pigs fed diets without Neoterramycin. Pigs fed diets containing KE- 01 had similar growth performance to that of pigs fed diets without KE-01. From d 14 to 35, pigs fed diets containing Neoterramycin had increased ADG compared with that of pigs fed diets without Neoterramycin. The ADG of pigs fed diets containing KE-01 did not differ from that of pigs fed diets without KE-01. There was a tendency for pigs fed KE- 01 to consume less feed, whereas pigs fed Neoterramycin ate more (KE-01 × Neoterramycin interaction, P<0.05). Pigs fed diets containing KE-01 tended to have improved F/G (P<0.07), compared with that of pigs fed diets without KE-01. Overall, d 0 to 35, pigs fed diets containing Neoterramycin had increased ADG and ADFI (P<0.01), compared with those of pigs fed diets without Neoterramycin. In addition, pigs fed diets containing KE-01 had similar ADG and ADFI to those of pigs fed diets without KE-01. Pigs fed diets containing KE-01 had improved F/G (P<0.03), compared with that of pigs fed diets without KE-01. In summary, the probiotic, KE-01, did not significantly increase ADG or ADFI, but did improve F/G because it slightly lowered feed intakes. Neoterramycin improved ADG, ADFI, and F/G, compared with those of diets without Neoterramycin in this study.
Keywords: Swine; Antibiotics; Pigs; Probiotic; Weanling pigs